Beneficial Effects of Dietary Nitrate on Endothelial Function and Blood Pressure Levels - Jenifer d’El-Rei; Ana Rosa Cunha; Michelle Trindade; Mario Fritsch Neves (International Journal of Hypertension)
Poor eating habits may represent cardiovascular risk factors since high intake of fat and saturated fatty acids contributes to dyslipidemia, obesity, diabetes mellitus, and hypertension. Thus, nutritional interventions are recognized as important strategies for primary prevention of hypertension and as adjuvants to pharmacological therapies to reduce cardiovascular risk. The DASH (Dietary Approach to Stop Hypertension) plan is one of the most effective strategies for the prevention and nonpharmacological management of hypertension. The beneficial effects of DASH diet on blood pressure might be related to the high inorganic nitrate content of some food products included in this meal plan. The beetroot and other food plants considered as nitrate sources account for approximately 60–80% of the daily nitrate exposure in the western population. The increased levels of nitrite by nitrate intake seem to have beneficial effects in many of the physiological and clinical settings. Several clinical trials are being conducted to determine the broad therapeutic potential of increasing the bioavailability of nitrite in human health and disease, including studies related to vascular aging. In conclusion, the dietary inorganic nitrate seems to represent a promising complementary therapy to support hypertension treatment with benefits for cardiovascular health.